Stability and Efficiency Optimisation of Renewable Energy Grid-Connected Systems Using Routh-Hurwitz Procedure - Hamdi Akhsan; Mega Kurnia; I. Ismet (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
The global demand for renewable energy is increasing along with the awareness of the environmental impact of using fossil fuels. This research investigates the application of the Routh-Hurwitz Procedure in enhancing the stability and operational efficiency of grid-connected renewable energy systems through systematic controller tuning and pole placement analysis. This study employed a Systematic Literature Review (SLR) based on PRISMA guidelines. Based on a literature review analysis of 27 articles from 2020-2025, it confirms that the Routh-Hurwitz method improves system stability by ensuring all poles are in the left-hand plane of the complex domain. The findings show that integrating Routh-based tuning with hybrid controllers such as PSO and ANN can reduce frequency oscillations, voltage and frequency stability are improved, and total harmonic distortion (THD) is reduced by as much as 1.967% and enhances frequency control within Â±0.1 Hz. Simulation results corroborate these conclusions and confirm the method's efficacy in actual PV and VSG-based systems. The Routh-Hurwitz criterion provides measurable enhancements in controller design for renewable energy integration and guarantees system stability by methodically assessing pole placement in the complex domain.